Factors associated with vaginal pathogens in primary health care patients in the Amazon region (Research, Society and Development, 2022)
Several factors cause fluctuation of the vaginal flora and may favor alterations by pathogens such as Gardnerella vaginalis, Candida sp., Trichomonas vaginalis and Neisseria gonorrhoeae. Objective: To determine the prevalence of vaginal pathogens and risk factors associated with women in Marabá-PA, between February and March 2020. Sample and methods: Cross-sectional study with a sample of 150 women. Fangs were analyzed by fresh examination, bacterioscopy, fungus culture and germ tube testing. For statistical analysis, the G-Test and the Chisquare test were used, considering significant p